Pengaruh Motivasi, Lama Pendidikan, Biaya Pendidikan, Kompetensi, Dan Reputasi Terhadap Minat Mahasiswa Akuntansi Untuk Mengikuti Pendidikan Profesi Akuntansi (PPAk) (Studi Empiris Pada Mahasiswa Universitas Muhammadiyah Surakarta) - Sito Resmi, Sevrina; , Drs. Wahyono, Ak, MA (2017)
The aim of this study was to find out the impact of motivation, length of education, cost of education, competence and reputation toward the students interest to join Accounting Profession Education (PPAk) of Accounting students at Muhammadiyah Universitas of Surakarta. Collecting the data canducted on 100 accounting students at Muhammadiyah University of Surakarta. Through giving questionnaire in this study analyzing the data used SPSS. The sampling technique used incidental sampling. In this research, technique of analyzing the data used Multiple Linier Regression. The result of data showed motivation has positive impact to students interest for joining PPAk. Length of education has negative impact to the student interest for joining PPAk. Cost of education has positive impact to the students interest for joining PPAk. Competence has positive impact to the students interest for joining PPAk. Reputation has positive to the students interest for joining PPAk.